2004
DOI: 10.1081/jdi-120038504
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Stroke in Chronic Dialysis Patients

Abstract: The overall prognosis of CH in the chronic dialysis population is poor. Patients with lower hemoglobin levels upon presentation and those performing PD after CH may have even worse prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…The prognosis of ICH in chronic dialysis patients is especially poor. The 30-day mortality rate has been reported to be as high as 67.3% (range 43.8–67.3%) [7,8,10,11,16,17,18]. The total 30-day mortality rate of our patients was 27.9%.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…The prognosis of ICH in chronic dialysis patients is especially poor. The 30-day mortality rate has been reported to be as high as 67.3% (range 43.8–67.3%) [7,8,10,11,16,17,18]. The total 30-day mortality rate of our patients was 27.9%.…”
Section: Discussionmentioning
confidence: 69%
“…In this study, we showed that the mortality rates were not significantly different for the EHD and CPD patients. In addition, our patients had a relatively lower mortality rate (total mortality 27.9%) than other series (mean mortality 62.1%, range 43.8–67.3%) [7,8,10,11,16,17,18]. The mean outcome score was 3 in the CPD and 2 in the EHD groups, respectively.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations